Liquid biopsy in TNBC: significance in diagnostics, prediction, and treatment monitoring - Sheng, Jiayi; Zong, Xiaolong (Frontiers in Oncology, 2025)
Breast cancer is the most common malignant tumor and the leading cause of mortality among women worldwide. Triple-negative breast cancer (TNBC) is recognized as t the most aggressive form of breast cancer, with a poor prognosis and a high mortality rate within two years. The role of tumor markers in facilitating the early diagnosis, treatment, and monitoring of therapeutic efficacy and prognosis in TNBC is well-established. Currently, tissue biopsy remains the standard clinical method for determining tumor histology and staging. However, the invasive nature of tissue biopsy often leads to poor patient compliance, especially when repeated biopsies are required. In contrast, liquid biopsy offers several advantages: it is non-invasive, sample collection is straightforward, it can reflect the overall tumor burden and heterogeneity, and it allows for real-time monitoring. The markers primarily encompass circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), microRNAs (miRNAs), long ncRNA (lncRNAs), exosome, and so forth. The present review aims to provide a comprehensive overview of the recent advancements and potential clinical applications of liquid biopsy technology in the context of TNBC.